Adoption Strategy for Electrical and Electronics (E&E) Small and Medium-Sized Enterprises (SMEs): Malaysia IR4.0 Perspective - Othman, Zakirah; Balakrishnan, Bavaani; Ahmad Zaidi, Mohamad Faizal; Wan Yahaya, Wan Ahmad Jaafar (Semarak Ilmu Publishing, 2022)
Many developing countries are facing difficulty in embracing Industrial Revolution 4.0 (IR4.0) technologies as it creates a challenging business environment for its manufacturing sector. It is vital for Malaysia, a developing country, in ensuring their manufacturing sector particularly Electrical and Electronics (E&E) Small and Mediumsized Enterprises (SMEs) are not left behind in the IR4.0. It is the mission that every E&E SMEs fully adopt IR4.0 technologies and drive towards sustainable and competitive economic growth. In doing so, concerns regarding the human dimension on digitally driven transformation initiatives are much more needed to be studied. Leveraging the human capabilities to the IR4.0 technologies is not only upskilling themselves in the field that is related to IR4.0 technologies, but also will decentralizing operations and coordinate processes. The IR4.0 will enable operations and processes equipped with extremely automated and digitized machines and robots that will be the parts of production in future. As such, this paper provides an insight on the research gap, the development of the manufacturing sector focusing on the E&E SMEs in Malaysia, the importance of IR4.0 and finally the significance of this research that explains the IR4.0 adoption